VISUAL LEXICONS FOR VISUALLY IMPAIRED STUDENTS: A SEMANTIC INTERPRETATION ANALYSIS - Payana, Wita Dwi; Helmi, Rahil (STKIP Siliwangi, 2025)
This study explores how students who are blind from birth comprehend and form semantic concepts, focusing specifically on the notion of a